An economic evaluation of vaccination in children against meningococcal infection in Moscow - S. V. Svetlichnaya; L. N. Mazankova; L. D. Popovich; L. A. Elagina (Izdatelstvo OKI, 2023)
Meningococcal infection (MI) is one of the most serious and life-threatening with an average mortality rate of 15 %. Infection accounts for the largest number of deaths of all infectious diseases among children under 17 years of age. Aim. Using simulation mathematical modeling to evaluate the potential epidemiological and economic benefits of vaccination against MI for children under the age of 1 year in Moscow with a Meningococcal (Groups A, C, Y and W-135) Polysaccharide Diphtheria Toxoid Conjugate Vaccine. Methods. The assessment of potential indicators of morbidity and mortality of children under the age of 1 year after vaccination in a hypothetic cohort was carried out, considering a period of the stable post-vaccination immunity. Data were compared with the indicators of the MI incidence in Moscow. Monetary equivalents of economic benefits are calculated, considering the cost of vaccination, direct and indirect costs. Results. It is possible to reduce the number of MI cases by 73 %, mortality by an average on 85 % after vaccination, in the horizon of 5 years of maintaining immunity tension, Vaccination of children under one year old can reduce the number of disability cases that occur after severe forms of infection. As a result, the economic impact from the mentioned disease can be reduced by 75 %. Conclusion. The resulting economic benefits in the future may significantly exceed the cost of vaccination. It seems expedient to accelerate the introduction of vaccination of children's contingents against MI.